Features of the Folk Ideas Reflection about Fate in the Signs and Superstitions of Social groups in Vladivostok - М. S. Kiseleva (Научный диалог, 2020)
The article is devoted to the signs and superstitions collected in 2014-2019 in Vladivostok and stored in the archives of the Department of Russian Language and Literature of the Far Eastern Federal University. The respondents were representatives of a number of social and professional groups: schoolchildren, students, doctors, sailors, fishermen, divers, taxi drivers and drivers. The following are considered in the texts: signs of the other world, foreshadowing a favorable or unfavorable outcome of events; special words / phrases that must / must not be said so as not to scare or attract good luck; actions that must / must not be performed; cumulative realization of signs, words and actions. It is proved that the signs and superstitions recorded among the Russian-speaking residents of Vladivostok are directly related to the complex of traditional ideas about fate. It is noted that superstitions are also based on the idea that a person is the creator of his own destiny, capable of attracting and retaining good luck, and building a dialogue with the other world. The assumption is made that the identified and described signs and superstitions have regional specificity: the territory of their existence is an outpost of Russia in the Far East. The changes that occur in omens and superstitions under the influence of the peculiarities of life and the organization of life of native speakers in a situation of cultural borderland are commented on.